Pendampingan Optimalisasi Perpustakaan Sebagai Sarana Meningkatkan Kesadaran Literasi Bagi Siswa SDN Sidorejo 01 - Hapsari, Estuning Dewi; Sucihati, Theresia Budi; Rizaldy, Dedy Richi; Khoiroh, Ni’matul Isti; Febriana, Amelia (Pakis Journal Institute, 2024)
The habit and interest in reading are activities that must be developed early in students. This is because reading will affect other students' skills. Libraries play an important role in providing reading facilities. The library at SDN Sidorejo 01 has not been managed well due to limited space and unorganized administration. Mentoring activities aim to improve the library's function as a place to explore knowledge, raise awareness of the importance of literacy skills, solve library administration problems, and provide library administration training. The method used in mentoring activities is APTE, which consists of needs analysis, training, action, and evaluation. Teachers and students participated in the activities enthusiastically and there was good cooperation between the service team and the school. Mentoring activities can increase interest in reading foster reading habits, and optimize library space. Apart from that, it can improve the reading skills of students who are still experiencing problems.